Posture d’auteur et médiation de l’œuvre : l’écrivain en porte-parole chez Antoine Volodine - Mette Tjell (Contextes)
The aim of this article is to highlight the importance of the rhetorical concept of ethos in the development of what Jérôme Meizoz (2007) calls a writer’s ‘posture’. The ambition is to show that the concept of posture exceeds the idea of positioning in the literary field, stating that a writer’s self-presentation is a central feature in the mediation process of the literary work in the social space. Using the example of the French writer Antoine Volodine and his fictional work, the article reflects upon the articulation of the posture in fictions whose story is not autobiographical. If one can assume that the discretion of a writer about his private life is a part of his posture, choosing fiction as a field of analysis requires taking into account the complex modalities in which the author manifests his/her presence in the text. The article applies the theoretical contributions developed by Ruth Amossy (2009) in the field of argumentation, where the ethos of the textual enunciator in a fictional corpus - the ‘auctorial ethos’ - is conceived as a means of influence on the reader, which can be deducted from different aspects of the text, such as themes, plot development, imagery and style.